Influence of two cooking methods of chard on imidacloprid and spinosad residues - Turaglio, María Eugenia; Navarro, Rosanna Graciela; Marcucci, Bruno; Herrera, Maria Eugenia; Becerra, Violeta Cristina (Ministerio de Desarrollo Agropecuario de Panamá, 2022)
Poster